Contribuições por meio de programação matemática para o (re)balanceamento de uma linha de montagem operando em modo degradado - Cavalli, Leonardo Torques (2021)
The balancing of assembly lines by mathematical models emerged as a viable proposal for production lines optimization, resulting in increased productivity, reduction of productive bottlenecks and other contributions. These models aim to equalize production times between workstations and workers, balancing the productive system. In addition, a new aspect of the production systems optimization segment proved to be of equal importance: the rebalancing of assembly lines. This research project fits into this segment, since it aims to obtain a mathematical model and solutions for the rebalancing of an assembly line operating in degraded mode of production, that is, with workstations in failure mode. This study was based on an assembly line installed in the region of Curitiba/PR; the line has two product segments, namely A and B. Within each segment, a series of product models are produced. For this project purpose, the four product models framed in A segment of this company were considered. These four models represent the totality of products in the A segment. This study aims to find a mathematical model and solutions for the rebalancing of this line for the operation in degraded mode, that is, when one (or more) workstation(s) goes(go) into failure mode. As a basic hypothesis, the studied assembly line has already undergone a process of optimization and balancing for normal conditions (without failure) and it operates in this way; thus, the characteristics of the existing line are known a priori. The historical data of failures of the seven stations in the assembly line were analyzed. First, the influence of workstations on the cycle time of the assembly line was evaluated, individually, in order to subsequently perform the studies for the two stations with the highest incidence of stopping failure conditions: stations 1 and 3. This fact generated three study scenarios: station 1 in failure mode; station 3 in failure mode; and stations 1 and 3 in failure mode, simultaneously. Based on these presented scenarios, four case studies took place, for the first phase of the mathematical model execution, in which the possibility of reallocating tasks was more / less restrictive. On the second phase of the model execution, a complementary study to the one addressed in the first phase was carried out, seeking to minimize the number of changes to the assembly line given a maximum allowed cycle time. Within each of the studies, the three scenarios presented were considered, leading to rebalancing solutions of the line operating in degraded mode of production.